PENERAPAN TEKNOLOGI DETEKSI KEBUNTINGAN DINI SAPI POTONG DI NAGARI SUNGAI KUNYIT KABUPATEN SOLOK SELATAN - Ferry Lismanto Syaiful; Khasrad Khasrad; Fauzia Agustin; Rusmana Rusmana (Buletin Ilmiah Nagari Membangun, 2019)
The objectives of this activity are: 1. increasing beef cattle productivity through early pregnancy detection technology in Sungai Kunyit Village, South Solok District, 2. increasing community knowledge and skills in the application of early pregnancy detection technology, and 3. transferring science and technology from tertiary institutions to the community in Sungai Kunyit Village, South Solok District. This activity was carried out in July 2019 in Sungai Kunyit Village, South Solok District. In this activity involved lecturers, students at Andalas University, breeders, and the community in Sungai Kunyit Village, South Solok District. While the methods used are lecture, question and answer, demonstration, coaching, and evaluation methods. While coaching and evaluating the activities carried out continuously. The results obtained from this activity are 1. the community and breeders are able to implement early pregnancy detection technology in beef cattle, 2. the high response of the community and breeders both in the extension activities and demonstration of early pregnancy detection technology, and 3. increased income of the community and breeders in Sungai Kunyit Village, South Solok District. This activity was attended by community leaders, village apparatus, and Sungai Kunyit village extension officers, South Solok. From the results of the action, it can be concluded that this activity is categorized as very successful and provides benefits to the community. This can be seen at the time when the events of the breeders/farmer groups and the community are substantial towards the development of beef cattle business.